2019
DOI: 10.3390/cancers11040564
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Neutrophils in Cancer: Going Pro

Abstract: The progression of cancer is not only about the tumor cell itself, but also about other involved players including cancer cell recruited immune cells, their released pro-inflammatory factors, and the extracellular matrix. These players constitute the tumor microenvironment and play vital roles in the cancer progression. Neutrophils—the most abundant white blood cells in the circulation system—constitute a significant part of the tumor microenvironment. Neutrophils play major roles linking inflammation and canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
236
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(259 citation statements)
references
References 159 publications
4
236
0
Order By: Relevance
“…Previously, two different neutrophil subpopulations were identified in lung tumor tissue, namely anti-tumorigenic, N1, and pro-tumorigenic, N2 PMNs, the latter accumulated as a result of increased TGFβ in the tumor microenvironment [12]. These descriptors have been expanded based upon context-specific neutrophil roles [21,35]. We found that, although BM-PCa increased neutrophil expression of TβRI, this increase had little impact on neutrophil-mediated PCa apoptosis despite increasing neutrophil viability.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previously, two different neutrophil subpopulations were identified in lung tumor tissue, namely anti-tumorigenic, N1, and pro-tumorigenic, N2 PMNs, the latter accumulated as a result of increased TGFβ in the tumor microenvironment [12]. These descriptors have been expanded based upon context-specific neutrophil roles [21,35]. We found that, although BM-PCa increased neutrophil expression of TβRI, this increase had little impact on neutrophil-mediated PCa apoptosis despite increasing neutrophil viability.…”
Section: Discussionmentioning
confidence: 74%
“…Previous evidence in other cancer types has demonstrated that cancer-induced neutrophil ROS and NETs contribute to tumor proliferation, demonstrated in other cancer types [19][20][21]. However, the consequences of neutrophil activation and direct neutrophil-BM-PCa interactions on tumor growth have not been fully explored.…”
Section: Neutrophils Regulate Pca Growth In Vitro Independently Of Tgfβmentioning
confidence: 99%
“…Several studies have provided compelling evidence for neutrophils' protumorigenic role, while others have advocated for neutrophils antitumor and antimetastatic potential . It is now generally accepted that neutrophils can acquire both pro‐ or antitumor function as part of an immunosuppressive switch occurring in cancer …”
Section: Introductionmentioning
confidence: 99%
“…8,9 It is now generally accepted that neutrophils can acquire both pro-or antitumor function as part of an immunosuppressive switch occurring in cancer. 10,11 Neutrophilia has been extensively described in cancer patients, but no clear correlation between absolute neutrophil count (ANC) and prognosis has been so far validated. 12,13 In contrast, the neutrophil-to-lymphocyte ratio (NLR) has been introduced as a strong prognostic factor for overall survival in many tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Hanahan and Weinberg have highlighted the significance of inflammation as an enabling hallmark in their updated version of 'Hallmarks of Cancer' [2]. Inflammatory cells within the tumour microenvironment play a role in promoting tumour progression and metastasis and a high index of innate immune cell infiltration is often associated with poor prognosis [3,4]. Moreover, it is known that inflammation caused by pre-existing chronic inflammatory conditions conveys a predisposition to cancer development (the 'extrinsic pathway'), whilst genetic events leading to neoplasia themselves promote the recruitment of inflammatory cells into tumours (the 'intrinsic pathway') [5].…”
Section: Introductionmentioning
confidence: 99%